Komunikasi Publik Intelijen dalam Mendukung Pemanfaatan Energi Nuklir di Indonesia - Rizkyagi Aanwijzi (Jurnal Ilmu Sosial dan Ilmu Politik)
Nuclear energy is currently an option to be applied in many countries, because it is considered to be a solution to the growing need for electrical energy. the need for electrical energy is getting bigger. However, until now there are still various challenges or problems to realize its utilization in Indonesia. to realize its utilization in Indonesia. One of the challenges in the development of development of nuclear energy is that there are still wrong perceptions related to the use of nuclear energy. nuclear energy. This perception to a certain extent results in the rejection of some people towards nuclear power plants. there is a rejection of some people towards nuclear power plants (Pembangkit Listrik Tenaga Nuklir). Nuclear Power Plant). Based on Law No. 17/2011 on State Intelligence State Intelligence, BIN plays a role in detection and anticipation efforts that threaten national security and interests. and national interests. Therefore, this research aims to analyze the role of intelligence in supporting accurate public communication, transparent, and fact-based public communication related to the utilization of nuclear energy in Indonesia, and analyze the causes of miscommunication in the utilization of nuclear energy in Indonesia. Indonesia. Qualitative research was chosen as the research method due to complexity of the problems associated with the utilization of nuclear energy in Indonesia, such as public perception, technical challenges, and government policies. government. The results of this study found that the construction of nuclear power plants in Indonesia faces a number of obstacles, including the lack of political will and strong regulations. Despite having fulfilled most aspects of required infrastructure, NPP has not yet become a priority issue.